Financial repression and debt liquidation in the USA and the euro area - Andreas Hoffmann; Holger Zemanek (Intereconomics, 2012)
Rising debt levels have caused a revival of financial repression in the euro area and the USA. The Federal Reserve directly represses US bond yields and assists in financing the state budget, resulting in an overall liquidation effect from falling bond yields of about three per cent of total government revenues and one per cent of GDP in 2011. In the euro area, the ongoing actions to contain the European debt crisis have also repressed interest rates, easing debt-servicing costs in all European countries and reducing the interest rate payments for the German government by about one to two per cent of total government revenues. This article argues that a slight rise in inflation could even liquidate German debt.
Keywords: 330; Haushaltsdefizit; Geldpolitik; Haushaltskonsolidierung; Inflation; USA; Eurozone